Network modelling and simulation tools - Rahman, Muhammad Azizur; Pakstas, Algirdas; Wang, Frank Zhigang (Elsevier, 2009)
Computer network technologies have been growing explosively and the study in computer networks is being a challenging task. To make this task easy, different users, researchers and companies have developed different network modelling and simulation (MS) tools. These network MS tools can be used in education and research as well as practical purposes. They vary with their characteristics. This paper reviews some of the most important network MS tools developed recently. This paper also shows a classification of the tools used in communications networks.
Keywords: Modelling; Network; Researcher; Simulation; Tools